Early Globalization and the Law of One Price: Evidence from Sweden, 1732-1914 - Mario J. Crucini; Gregor W. Smith (East Asian Economic Review (EAER), 2016)
We review research using departures from the law of one price to measure the advent of globalization in Europe and Asia. In an application, we then study the role of distance and time in statistically explaining price dispersion across 32 Swedish towns for 19 commodities from 1732 to 1914. The resulting large number of relative prices (502,689) allows precise estimation of distance and time effects, and their interaction. We find an effect of distance that declines significantly over time, beginning in the 18th century, well before the arrival of canals, the telegraph, or the railway.
Keywords: E37; F61; N70; 330; Distance Effect; Law of One Price; Globalization; Historical Price Convergence; Market Integration in Sweden